SEJARAH MASUK DAN BERKEMBANGNYA AGAMA ISLAM DI LOGHIYA MUNA ABAD XVI-XVII - Erniati Erniati; Evang Asmawati, Sitti Hermina (Journal Idea of History, 2019)
This study aims to describe the history of the entry and development of Islam in Loghiya in the XVI-XVII centuries. The method used in this study was the historical method proposed by Kuntowijoyo which consisted of five stages, namely: (1) Topic selection (2) Source heuristics (3) Source verification (4) Source interpretation and (5) Historiography. The results showed that: (1) The initial entry of Islam in Loghiya was brought by Sheikh Abdul Wahid in 1527 AD when the people still adhered to animism and dynamism. Islamic symbols were then continued by Firus Muhammad in 1614 AD who taught about fasting Ramadan. Furthermore, the spread of Islam by the Shari'a was carried out by Syarif Muhammad in 1643 AD (2) Pathways used in the spread of Islam in Loghiya through: (a) Trade routes, (b) Arts routes, and (c) Paths of Sufism. (3) The development of Islam in Loghiya could be seen through three periods namely: (a). Period of Sheikh Abdul Wahid in 1527 AD, (b) Period of Firus Muhammad in 1614 AD, (c) Period of Islamization carried out by Syarif Muhammad / Said Raba in 1643 AD Keyword: History, Dissemination, Development, Islam and Loghiya